An international validation study of two achievement goal measures in a pharmacy education context - Alrakaf, Saleh (Dove Medical Press, 2014)
BACKGROUND: Achievement goal theory helps us understand what motivates students to participate in educational activities. However, measuring achievement goals in a precise manner is problematic. Elliot and McGregor’s Achievement Goal Questionnaire (AGQ) and Elliot and Murayama’s revised Achievement Goal Questionnaire (AGQ-R) are widely used to assess students’ achievement goals. Both instruments were developed and validated using undergraduate psychology students in the USA. METHODS: In this study, our aims were to first of all, assess the construct validity of both questionnaires using a cohort of Australian pharmacy students and, subsequently, to test the generalizability and replicability of these tools more widely in schools of pharmacy in other English-speaking countries. The AGQ and the AGQ-R were administered during tutorial class time. Confirmatory factor analysis procedures, using AMOS 19 software, were performed to determine model fit. RESULTS: In contrast to the scale developers’ findings, confirmatory factor analysis supported a superior model fit for the AGQ compared with the AGQ-R, in all countries under study. CONCLUSION: Validating measures of achievement goal motivation for use in pharmacy education is necessary and has implications for future research. Based on these results, the AGQ will be used to conduct future cross-sectional and longitudinal analyses of the achievement goals of undergraduate pharmacy students from these countries.